Unleashing the Female Voice: Madeline Miller's Circe and Laura Shepperson's Phaedra: A Novel - ŞAHİN, TUĞÇENUR (İstanbul Kültür Üniversitesi, 2024)
This thesis examines the portrayal of mythological female figures in the classical Greek texts written within the patriarchal discourses and explores how these portrayals show differences in the contemporary retellings of women writers. The perception of women in ancient Greek society, imposed gender roles and the condemnation of female sexuality and their body prevent women to live as individuals who have voice, agency and freedom. This oppression on women is reflected on ancient Greek literature, dominated by male authors, as stereotypical female characters and thus patriarchal ideology othering women establishes a presence in culture through writing. Increasing number of women writers in literature enable the production of feminist works that demolish the artificial gender roles and also enable the narration of women by women. In this regard, women writers' retellings in which they revise mythological female figures, carry an enormous significance as they indicate how deeply the patriarchal ideology is grounded in literature and how women writers' struggle to overturn this partial way of thinking that still continues in this present day. This thesis aims to shed light on the patriarchal discourses in the classical works presenting two mythological female characters, Circe and Phaedra and to illustrate the contemporary women writers' attempt to shatter these discourses through their retellings written from a feminist point of view. Through the selected two novels; Madeline Miller's Circe and Laura Shepperson's Phaedra: A Novel, I intend to point out the role of feminist retellings, focusing on female experience, voice and autonomy, in challenging the literary works written within the androcentric viewpoint.
Kadın Sesinin Salıverilişi: Madeline Miller'dan Circe ve Laura Shepperson'dan Phaedra: A Novel
Yüksek lisans tezi.
Keywords: Patriarchal discourse; Feminism; Retelling; Greek Mythology; Madeline Miller; Circe; Laura Shepperson; Phaedra: A Novel